Neue Freunde: Über Freundschaft in Zeiten von Facebook - Vedder, Björn (transcript, 2017)
Friendships have never been more popular than today. They are considered to be an essential ingredient for a good and happy life. Many people have lots of friends, too – yet they don't really feel the sense of happiness the social media have been promising. Why is that? In his time diagnosis of friendship, Björn Vedder combines philosophical contemplations with the analysis of pop culture material as well as classics of literature. He shows us what friendship can mean today, how it can be successful (even being our own best friends) and why Facebook friends are real friends. While doing so, he takes today's pessimistic cultural criticisms seriously without sharing their defeatism but instead offering ways how to overcome the pathologies of modern friendship.